Предмет: Алгебра,
автор: Shimmery12
Преобразовать в многочлен:
1. (y-8)(2y-1)-(3y+1)(5y-2)
2.(x+2)2-(x-3)(x+3)
3. (y-2)(y+3)-(y-1)2+(5-y)(5+y)
4. (x-2)2+(x-1)(x+2)
Ответы
Автор ответа:
2
1.(y-8)(2y-1)-(3y+1)(5y-2)=(2y²-y-16y+8)-(15y²-6y+5y-2)=2y²-y-16y+8-15y²+6y-5y+2=-13y²-16y+10
2.(x+2)²-(x-3)(x+3)=(x²+4x+4)-(x²-9)=x²+4x+4-x²+9=4x+13
3.(y-2)(y+3)-(y-1)²+(5-y)(5+y)=(y²+3y-2y-6)-(y²-2y+1)+(25-y²)=y²+3y-2y-6-y²+2y-1+25-y²=-y²+3y+18
4.(x-2)²+(x-1)(x+2)=(x²-4x+4)+(x²+2x-x-2)=x²-4x+4+x²+2x-x-2=2x²-3x+2
Похожие вопросы
Предмет: Биология,
автор: hajryllaevasadbek
Предмет: Химия,
автор: asurovamilana30
Предмет: Химия,
автор: duhnopavel7
Предмет: История,
автор: Аноним
Предмет: Математика,
автор: алыерозы228